Urgensi Managemen Pendidikan Islam Dalam Pembinaan Akhlak Siswa - Fauziyati, Wiwin Rif’atul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of preparing this manuscript is to determine the urgency of Islamic education management in developing student morals. This research began with a comprehensive literature review, involving scientific literature, books, related articles, and previous studies. The main data sources include scientific literature, interviews with Islamic education experts, and analysis of school policy documents. In data analysis, we categorized findings from various sources to describe the urgency of Islamic education management in fostering student morals, with a focus on key concepts and their impact. The result of this work is the urgency of Islamic education management in fostering student morals that stand out in the complexity of the world of education. The moral development of students is considered urgent, with good character as the main basis for guiding them. Islamic education plays a central role in shaping students' morals and ethics, with Islamic-based educational management providing a positive impact on character formation according to the values of the Qur'an and Sunnah. A balance between efficient management and quality moral development is the key to creating a holistic educational environment according to Islamic teachings.